Biomechanical effects of patellar taping in subjects with patellofemoral pain syndrome (PFPS) - Javid Mostamand; Daniel Bader; Zoee Hudson (Vesnu Publications, 2010)
Introduction: Patellofemoral pain syndrome (PFPS) is one of the most common musculoskeletal disorders affecting adults. Patellar taping provides an effective treatment in alleviating the symptoms of a high proportion of subjects who present with PFPS. The mechanisms of pain reduction have not completely been established, although it may be related to alteration in the kinetics of patellofemoral joint following taping. Materials and Methods: A Case-control study was designed to examine the effects of patellar taping on the biomechanics of the patellofemoral joint in subjects with PFPS. Patellofemoral joint reaction force (PFJRF) of eighteen subjects with PFPS and the similar number of healthy controls were assessed using a motion-analysis system and one force plate. This procedure was performed on the affected knee of subjects with PFPS, before, with and finally after patellar taping during the eccentric phase of single leg squatting. Unaffected knee of subjects with PFPS and both knees of control group were also undergone the similar procedure. Results: The result revealed that the mean values of PFJRF prior to taping (2025 ± 347 N) had decreased significantly following a period of taping and exercises (1720 ± 303 N) (P < 0.05). The PFJRF values of affected knees of subjects with PFPS before application of tape, and healthy controls (1922 ± 398 N) were not significantly different (P > 0.05). Conclusion: The corresponding decrease of pain level accompanied with the decreased kinetics, may explain the mechanism of pain reduction following patellar taping in subjects with PFPS